Resistive switching transparent SnO2 thin film sensitive to light and humidity - Kalateh, Asiyeh; Jalali, Ali; Kamali Ashtiani, Mohammad Javad; Mohammadimasoudi, Mohammad; Bastami, Hajieh; Mohseni, Majid (Scientific reports, 2023)
Designing and manufacturing memristor devices with simple and less complicated methods is highly promising for their future development. Here, an Ag/SnO 2 /FTO(F-SnO 2 ) structure is used through the deposition of the SnO 2 layer attained by its sol via the air-brush method on an FTO substrate. This structure was investigated in terms of the memristive characteristics. The negative differential resistance (NDR) effect was observed in environment humidity conditions. In this structure, valance change memory and electrometalization change memory mechanisms cause the current peak in the NDR region by forming an OH − conductive filament. In addition, the photoconductivity effect was found under light illumination and this structure shows the positive photoconductance effect by increasing the conductivity. Memristivity was examined for up to 100 cycles and significant stability was observed as a valuable advantage for neuromorphic computing. Our study conveys a growth mechanism of an optical memristor that is sensitive to light and humidity suitable for sensing applications.